The Effect of Six Weeks of Patella Taping on Pain in Women with Knee Osteoarthritis - Maryam Alikhani; Hamid Tabatabai (Biyumikānīk-i varzishī, 2024)
Objective This study aimed to assess the effect of six weeks of patella taping on pain levels in women with knee osteoarthritis. Methods This research was an applied, semi-experimental study. The study population consisted of middle-aged women aged 30 to 50 years. Using convenience sampling, 30 women with knee osteoarthritis, referred to an orthopedic clinic in Tehran, were selected as the study sample. The participants were randomly assigned to either the experimental group (15 women) or the control group (15 women). Pain was measured using the Visual Analog Scale (VAS). The experimental group received patella taping for six weeks. Data analysis was performed using Paired-Sample T Test for intra-group comparisons and Analysis of Covariance (ANCOVA) for inter-group comparisons. All analyses were conducted using SPSS version 26, with a significance level set at 0.05. Results The experimental group showed a significant reduction in pain levels, with a mean difference of 2.91, a t-value of 2.67, and a significance level of p=0.04 between the pre-test and post-test. In contrast, the control group exhibited a mean difference of 0.11, a t-value of 0.74, and a significance level of p=0.32, indicating no significant effect. The ANCOVA results also revealed a significant difference between the two groups in the post-test (p=0.03). Conclusion The findings suggest that patella taping has a positive effect on reducing knee pain in women with osteoarthritis. Therefore, sports trainers and physiotherapists are encouraged to consider patella taping as a non-pharmacological intervention to alleviate pain in women with knee osteoarthritis.